(b) (g compose f)(x)

label Algebra
account_circle Unassigned
schedule 1 Day
account_balance_wallet $5

Use 
f(x) = 5x − 2
 and 
g(x) = 4 − x2
 to evaluate the expression.
(a)    
(f of g)(x)

 (b)    (g of f)(x)

 
Jul 1st, 2015

Thank you for the opportunity to help you with your question!

(f of g)= 5(4-x^2)-2

=20-5x^2-2

=18-5x^2


(g of f)= 4-(5x-2)^2

=4-25x^2+20x-4

=20x-25x^2

Please let me know if you need any clarification. I'm always happy to answer your questions.
Jul 1st, 2015

Did you know? You can earn $20 for every friend you invite to Studypool!
Click here to
Refer a Friend
...
Jul 1st, 2015
...
Jul 1st, 2015
Jun 24th, 2017
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer